Research into the causes of overheating of bearings and solving the problem of further operation of a 450 kVA short break diesel-generating set at Belgrade Airport - Žegarac, Nikola P. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The paper presents the research into the causes of increased heating in bearings and troubleshooting further exploitation of a Short Break diesel generating set with a power of 450 kVA at Belgrade Airport. The diesel engine is a type of Short Break, which means that in the event of an interruption in the electricity supply from the city network, there is a certain interruption of about 40 seconds until diesel generators start to supply electricity to the equipment and systems at Belgrade Airport. The main function of the diesel engine is to serve as a backup source power supply for devices and systems in case of limited visibility (lighting around the runway and many other devices and systems).